Mast cell tryptase, a potent inflammatory mediator, requires heparin for enzymatic activation - Lindahl, Susanne (SLU/Dept. of Molecular Biosciences, 2007)
Mast cell tryptase, a tetrameric serine protease stored in mast cell granules in complex with heparin proteoglycan or chondroitin sulphate proteoglycan, is an important effector molecule in inflammatory reactions like allergies and asthma. In this study we have investigated the requirements for activation of human Î²I-tryptase and Î²II-tryptase, the major tryptases of human mast cells. Î²I-tryptase and Î²II-tryptase differ in only one amino acid, no. 102, where Î²I-tryptase has an asparagine (Asn) residue which is also site for glycosylation while Î²II-tryptase has a lysine (Lys) residue and lacks glycosylation at that site. We found that both Î²I-tryptase and Î²II-tryptase were dependent on heparin for activation and that optimal activity for Î²I-tryptase occurred at acidic pH while activation of Î²II-tryptase was less pH-dependent. Both Î²I-tryptase and Î²II-tryptase had a strong affinity for heparin-Sepharose at acidic pH but this affinity decreased at neutral pH. The Î²-tryptases both showed a bell shaped dose response curve for heparin induced activity. These results, taken together with results from a parallel study indicate an important role for heparin in the activation of human Î²-tryptase.